Luck of the draw - Clayborn, Kate (Clayborn, Kate. Chance of a lifetime romance., 2024)
"Sure, winning the lottery allows Zoe Ferris to quit her job as a cutthroat corporate attorney but no amount of cash will clear her conscience about the way her firm treated the O'Leary family in a wrongful death case. So she sets out to make things right only to find gruff, grieving Aiden O'Leary doesn't need or want her apology. He does, however, need something else from her. Something Zoe is more than willing to give, if only to ease the pain in her heart, a sorrow she sees mirrored in his eyes"--